PENGEMBANGAN MEDIA INTERAKTIF VIDEO ANIMASI BERBASIS POWTOON MATERI BAGIAN TUBUH HEWAN BESERTA FUNGSINYA PADA PEMBELAJARAN IPA KELAS IV SEKOLAH DASAR - Aulia Salsabillah (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
This study aims to develop videoscribe animation learning media in science learning class IV Elementary School. The subjects of this study were fourth grade students of SDN Slipi 15 Pagi. This study uses ADDIE's Research and Development (R&D) model, namely Analysis, Design, Development, Implementation, Evaluation. The instrument used is a questionnaire. Media product validation was carried out by two experts, namely: material experts and media experts. The validation results by media experts scored 97% in the very good category (SB). The results of validation by material experts scored 90% in the very good category (SB). From the results of the two expert validations, a score of 93% was included in the very good category (SB). Then in product trials carried out by three stages, namely: one to one, small group and field test. The results of the one to one stage trial got a score of 79% in the very good category (SB). The results of the small group trial got a score of 95% in the very good category (SB). The results of the field test stage got a score of 94% in the very good category (SB). From the three product trial results, a score of 89% was included in the very good category (SB) so that it was suitable for use as a medium in learning science about animal body parts and their functions in class IV SD.